A small physiological electric field mediated responses of extravillous trophoblasts derived from HTR8/SVneo cells: involvement of activation of focal adhesion kinase signaling. - Juan Zhang; Rongmei Ren; Xuefeng Luo; Ping Fan; Xinghui Liu; Shanshan Liang; Lei Ma; Ping Yu; Huai Bai (PLoS ONE, 2014)
Moderate invasion of trophoblast cells into endometrium is essential for the placental development and normal pregnancy. Electric field (EF)-induced effects on cellular behaviors have been observed in many cell types. This study was to investigate the effect of physiological direct current EF (dc EF) on cellular responses such as elongation, orientation and motility of trophoblast cells. Immortalized first trimester extravillous trophoblast cells (HTR-8/SVneo) were exposed to the dc EF at physiological magnitude. Cell images were recorded and analyzed by image analyzer. Cell lysates were used to detect protein expression by Western blot. Cultured in the dc EFs the cells showed elongation, orientation and enhanced migration rate compared with non-EF stimulated cells at field strengths of 100 mV/mm to 200 mV/mm. EF exposure increased focal adhesion kinase (FAK) phosphorylation in a time-dependent manner and increased expression levels of MMP-2. Pharmacological inhibition of FAK impaired the EF-induced responses including motility and abrogated the elevation of MMP-2 expression. However, the expression levels of integrins like integrin α1, α5, αV and β1 were not affected by EF stimulation. Our results demonstrate the importance of FAK activation in migration/motility of trophobalst cells driven by EFs. In addition, it raises the feasibility of using applied EFs to promote placentation through effects on trophoblast cells.